A Systematic Approach to Evaluating Corrective Actions to Create Safety Culture in Nuclear Industry - Rudenko, V. A.; Ozhereliev, V. D.; Evdoshkina, Yu. A.; Tsuverkalova, O. F.; Setrakov, A. N. (Глобальная ядерная безопасность, 2022)
This article examines the role of safety culture and the direction of its formation to ensure the efficiency of the nuclear industry enterprises. There are two main categories to be analyzed - consciousness and self-control, it analyses their interrelation, mutual influence. We use a non-standard approach for this problem - the method of analyzing hierarchies. As a result of the calculations, a matrix of global priorities is constructed, which allows us to rank by significance activities aimed at overcoming destructive factors. The most significant event is considered to be the constant expansion of the information field. The results obtained should form the basis of a strategy for creating and improving the level of safety culture at nuclear power plants as the riskiest industrial facilities.